2016
DOI: 10.1038/srep33506
|View full text |Cite
|
Sign up to set email alerts
|

Diverse ruthenium nitrides stabilized under pressure: a theoretical prediction

Abstract: First-principles calculations were performed to understand the structural stability, synthesis routes, mechanical and electronic properties of diverse ruthenium nitrides. RuN with a new I-4m2 symmetry stabilized by pressure is found to be energetically preferred over the experimental NaCl-type and ZnS-type ones. The Pnnm-RuN2 is found to be stable above 1.1 GPa, in agreement with the experimental results. Specifically, new stoichiometries like RuN3 and RuN4 are proposed firstly to be thermodynamically stable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
(67 reference statements)
3
20
0
Order By: Relevance
“…In the current study mean liver stiffness measure was similarly observed to be 5, 8.43, 11.3 and 13.2 kPa, for study subjects with F0-F1, F2, F3 and F4 fibrosis respectively. A significant increase in mean fibroscan reading from F2 to F3 (p value = 0.002), and a marginal association between increase in liver stiffness measure readings from F2 to F4 (p value = 0.09) was noted, which is comparable to the findings of G. Zhang et al [16].…”
Section: Discussionsupporting
confidence: 86%
“…In the current study mean liver stiffness measure was similarly observed to be 5, 8.43, 11.3 and 13.2 kPa, for study subjects with F0-F1, F2, F3 and F4 fibrosis respectively. A significant increase in mean fibroscan reading from F2 to F3 (p value = 0.002), and a marginal association between increase in liver stiffness measure readings from F2 to F4 (p value = 0.09) was noted, which is comparable to the findings of G. Zhang et al [16].…”
Section: Discussionsupporting
confidence: 86%
“…Ru alloys have been extensively studied at extreme conditions (experimentally and theoretically) to investigate possible ultra-hard materials 11–13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, we are unaware about the existence of linear nitrogen chains containing more than six nitrogen atoms, which have been reported hitherto. Interestingly, polytetrazene-type nitrogen chains were predicted to exist in the high-pressure phase with N 2 H stoichiometry, in BeN 4 and in RuN 4 17 , 28 , 63 . In these chains, the ratio of the number of single to double N–N bonds (3:1) is the same as that we found in FeN 4 , however the structures are different.…”
Section: Resultsmentioning
confidence: 99%